THE EFFECT OF COMPENSATION, WORKLOAD AND ORGANIZATIONAL COMMITMENT ON THE PERFORMANCE OF NON-ASN STATE HIGH SCHOOL TEACHERS IN BATAMCITY WITH ACHIEVEMENT MOTIVATION AS AN INTERVENING VARIABLE - Sri Rahayu; Bambang Satriawan; Nolla Puspita Dewi (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of compensation, workload, and organizational commitment on the performance of non-ASN state high school teachers in Batam City, with achievement motivation as an intervening variable. The background of the study is based on the phenomenon of low performance of some non-ASN teachers as indicated by the increasing proportion of performance assessments in the